Practical Guidance of Islamic Law for managing potential Future covid-19 relapses - Ridwan O., Olagunju-Ibrahim,; Hussein F, Ahmad; Taofeeq A, Abdulraheem; Kawthar A, Hamzat-Umar; Mamudat I, Olohungbebe; Danjuma Y, Ismail (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2026)
Abstract The covid-19 pandemic with all its underlined devastating medical challenges has come and gone. This study however brings back the painful memories of the pandemic with a view to examining what indices may again have the potential to bring about its possible future outbreak. The study particularly aims at exploring the checkmating roles of Islamic law on this global life-threatening calamity. The objectives in this work are to propose an integration of the therapeutic guidance of Islamic law with orthodox medical contributions of scientists (vaccinations, majorly). The hybrid of these twin variables is considered imminent to offer better relief and wellness when needed. This is moreso that the so-called scientific interventions, while the Covid-19 lasted, were not free from harsh side effects such as the inflammation of the heart muscle and the lining after the heart. This research employs a qualitative approach through library research, utilizing, content analysis of literature related to the subject of focus. Findings indicate that though the pandemic’s intensity has long subsided, factors such as increased human-animal interaction, urban overcrowding and climate change among others can contribute to reoccurrence of the pandemic at any time. The work further finds that plethora of guidelines exist in the Qur’an and Sunnah which offer Islamic way-out from illnesses and pandemics.